The Geographies and the Temporal Trends/Dynamics of Urban Sprawl in a Suburban Area - Kavirathna, Guwani Erangi; Karunarathna, Ananda Y (Urban Planning and Construction, 2026)
Urban sprawl refers to the expansion of cities towards the countryside, associated with developed infrastructure facilities and transportation networks. Thus, this study aims to analyze the geospatial patterns/dynamics of the urban sprawl, examine the temporal patterns/dynamics of the urban sprawl, and investigate the causative factors of the urban sprawl in the Homagama Divisional Secretariat Division (DSD), Sri Lanka (1992–2022). Accordingly, this study was completely based on digitized buildings using Geographic Information System (GIS), and Remote Sensing (RS). Shannon’s Entropy value and the intensity of urban sprawl were used to analyze the geospatial patterns of urban sprawl. Results revealed a transition pattern of building distribution from compact to dispersed patterns, with slow expansion intensity. Building density and sprawl direction were employed to examine the temporal pattern of urban sprawl. Accordingly, middle building density areas are distributed throughout the study area. Very high building density areas have agglomerated in specific areas associated with developed infrastructure facilities. In the evolution of directional expansion, the buildings in 1992 primarily expanded to the southwest. After this pattern gradually spread towards the southwest, northward, and northeastward directions from 2017 to 2022. Population density and transportation network were used to investigate the causative factors. The population density took an upward trend with the intensification of urban sprawl. The buildings were gradually increasing along primary and secondary roads with accessibility and connectivity. Based upon the findings demonstrated, this study suggests a sustainable urban master plan with an appropriate urban policy should be considered/established in order to manage this unplanned urban sprawl and mitigate socio-environmental challenges. Hence, this study sheds light on demonstrating the specific patterns of unplanned urban sprawls of suburb geographies in a low-middle income developing country.